Phase-field modeling for freeze crystallization in a binary system - Huang, Xiaoqian; Galfré, Aurélie; Couenne, Françoise; Cogné, Claudia (Computer Aided Chemical Engineering, 2024)
This article investigates the freeze crystallization process from water-sodium chloride solution. The freeze crystallization process (from 273.15 K to the eutectic point 252.05 K) generates two phases: a solid phase comprising solely ice and a liquid phase consisting of a concentrated solution. The phase-field model approach is used to simu-late the ice crystal growth from a solution and its specific dendritic structure. The ab-sence of solute in the solid phase is challenging to model because of i) the strong non-ideality of the system; ii) the requirement of a continuous salt profile in the interface. The article aims to provide a straightforward approach to address this complexity and study the partition coefficient impact on solute distribution.